A intensificação das contradições das práticas institucionais induzidas pela atual cultura da universidade pública: o caso da FEMEC-UFU - Stopa, Lia Bernardes Basile Silveira (Universidade Federal de São Carlos, 2011)
This work has the objective to analyze the perspective of the research professors (―professores pesquisadores‖) about the possible consequences of the work intensification, on the graduate level, for the teaching and other activities at the undergraduate level. Such process occurred in the context of the adjustment of the national economy to the capital mundialization, and the reform of the State apparatus. It established a north to the reconfiguration of the identity of the public universities and brought consequences for the teaching work. To meet our objective, 13 semi-structured interviews were realized with the teaching personnel of FEMEC-UFU. This university have been chosen with basis on the data and the research analysis of Sguissard and Silva Júnior, as published in their book ―O trabalho intensificado nas Federais: pós-graduação e produtivismo acadêmico - 2009. The results presented in this book and the fact that the FMEC graduate course received grade 6 are suggestive of a high productivity as well as an intensification of the teaching work. The interviews were analyzed by a systematization of subtopics arisen from an attentive lecture. These subtopics CAPES, work intensification, techno-scientific production (academic productivism), public-private partnership (PPP), young professors versus old professors, philosophy and organization of the teaching unity... or department... are closely related to our objective and to our research object. Such procedures revealed the complexity as well as the contradictions existing in the relationship between the graduate and undergraduate university practices. Ou research hypothesis was partially corroborated by the analysis of the data we obtained. In view of the current conjuncture of the work of the FEMEC-UFU professor-engineer, it is possible to affirm that there is indeed a tendency that his graduate activities superimpose the activities he might develop at the undergraduate level. However, in view of changes on the work system, some professors that already have a consolidated career have chosen to leave the graduate teaching and be active on the research work and on the undergraduate teaching. In this way, these professors believe to be to more loyal to their values and education ideals. There some professors that left the graduate work to seek recognition by working at the coordination level of a new undergraduate course. Moreover, another aspect that appears from our study is that the work of the ―professor-engineerresearcher‖ [in partnership with some industry] consumes most of the time that he could dedicate to his activities at the undergraduate level, and in some cases, at the graduate level. It is important to remember that such ―extra-school‖ work is induced by public bids, reconfiguration of public universities, and the incentive of the PPP s, in a context of increasing demand of both the productive and enterprise sectors for technological knowledge. Also, assuming adminstrative positions and, therefore, participating of the university administration difficult developing teaching activities in the graduate or undergraduate levels. The immaturity or the unpreparedness of students were also considered as factors that render the work at the graduate or undergraduate levels a strenuous task. Finally, in the vision of some professors, the exigencies of the work at the graduate level tend to be considered natural and even justified. Such demands could, in some circunstances, make possible a better sinergy between the two levels of education, graduate and undergraduate. The laboratories [thereby, the practical classes] could be greatly improved. Therefore, more students could be atract to the courses it worth to remember that, after all, students are important inputs for the researches and publications.
Keywords: Reforma do estado; Universidades e faculdades públicas; Relação graduação-pós-graduação; Produtivismo acadêmico; Intensificação do trabalho; Reforma do estado; State reform; Public university; Relationship undergraduate-graduate teaching; Academic productivism; Work intensification; CIENCIAS HUMANAS::EDUCACAO